Epigallocatechin-3-gallate selenium nanoparticles for neuroprotection by scavenging reactive oxygen species and reducing inflammation - Wang, Yiming; Luo, Wenqi; Lin, Feng; Liu, Wanguo; Gu, Rui (Frontiers in Bioengineering and Biotechnology, 2022)
Purpose: Spinal cord injury (SCI) is a severely crippling injury. Scavenging reactive oxygen species (ROS) and suppressing inflammation to ameliorate secondary injury using biomaterials has turned into a promising strategy for SCI recuperation. Herein, epigallocatechin-3-gallate selenium nanoparticles (EGCG-Se NP) that scavenge ROS and attenuate inflammation were used for neuroprotection in SCI. Methods: EGCG-Se NP were arranged using a simple redox framework. The size, morphology, and chemical structure of the EGCG-Se NP were characterized. The protective effect of EGCG-Se NP for neuroprotection was examined in cell culture and in an SCI rat model. Results: EGCG-Se NP could promptly scavenge excess ROS and safeguard PC12 cells against H2O2-induced oxidative harm in vitro. After intravenous delivery in SCI rats, EGCG-Se NP significantly improved locomotor capacity and diminished the injury region by safeguarding neurons and myelin sheaths. Component studies showed that the main restorative impact of EGCG-Se NP was due to their ROS-scavenging and anti-inflammatory properties. Conclusion: This study showed the superior neuroprotective effect of EGCG-Se NP through ROS sequestration and anti-inﬂammatory capabilities. EGCG-Se NP could be a promising and effective treatment for SCI.